IMPROVING CHILDREN’S PROBLEM-SOLVING SKILLS THROUGH JAVANESE TRADITIONAL GAMES - Iswinarti Iswinarti; Dewi Retno Suminar (Jurnal Cakrawala Pendidikan, 2019)
Nowadays, most children play digital games. Digital games, despite their advantages, have gradually eroded the existence of traditional games. Although both digital and traditional games comprise the values of problem-solving learning for children, traditional games offer more benefits in terms of the embodiment of local wisdom. This study aimed at encompassing the influence of Javanese traditional games such as bekelan, congklak lidi, and selentikan on the improvement of children’s problem-solving skills. This research was done employing quasi-experimental design involving 72 school-age children ranging from 9 to 11 years old, who studied at primary schools. The subjects of this study consisted of four experimental groups. Three groups played bekelan, congklak lidi, selentikan games respectively and the other group was assigned as the control group. The treatment was done for three weeks divided into six sessions. The findings showed that there was a significant improvement between the result of the pre-test and that of the post-test for these three games. The analysis results using One Way ANOVA showed that there was a difference in the improvement of problem-solving skills among groups (F(17) = 5.032, p .01). Due to its superiority, Javanese traditional games are potential to be an alternative media in improving children’s problem-solving skills.